Studi Keperilakuan Individu dalam Menggunakan Sistem Informasi Berbasis Teknologi - Tri Rahayu Widyaningrum; M. Iswahyudi (STIE Malangkucecwara, 2017)
This study aims to examine the factors that influence behavior interest toward individual behavior in using technology based information system. This research uses Model Technology Acceptance Model (TAM) with the addition of system quality construct. This research uses survey method and take sample as many as 50 individuals working in companies engaged in finance in Banyuwangi. Test data using WarpPLS 3.0 application. The result of this research is construct perception of ease and quality of system have positive effect to behavior interest. Furthermore, interest in behavior positively affect the behavior of individuals in using technology-based information systems. Perceptions of usefulness and attitudes have a positive effect on behavioral interest but are not significant. The implication of this research is that information technology and management information system providers should consider more about the perception of convenience, system quality, behavioral interest and individual behavior.